ESSR Consensus Document for Detection, Characterization, and Referral Pathway for Tumors and Tumorlike Lesions of Bone - Lalam, Radhesh; Bloem, Johan L; Noebauer-Huhmann, Iris M; Wörtler, Klaus; Tagliafico, Alberto; Vanhoenacker, Filip; Vasilevska Nikodinovska, Violeta; Sanal, Hatice Tuba; Woude, Henk-Jan van der; Papakonstantinou, Olympia; Åström, Gunnar; Davies, Mark; et al. (Georg Thieme Verlag KG, 2017)
Benign bone tumors are rare but are more common than primary malignant bone tumors. The early accurate diagnosis and reliable differentiation of these rare benign tumors and tumor mimickers from the even rarer malignant tumors with subsequent appropriate treatment or watchful waiting is crucial for the clinical outcome. Bone tumors are often a source of diagnostic and therapeutic uncertainty. Thus this European Society of Musculoskeletal Radiology consensus document is intended to help radiologists in their decision making and support discussion among clinicians who deal with patients with suspected or proven bone tumors. Evaluating these tumors starts with a patient history and physical examination. Radiography is the principal imaging modality and often can reliably diagnose a benign bone tumor by providing information about localization, matrix, aggressiveness, size, and (potential) multiplicity. In a significant number of cases, additional imaging is not necessary. Potentially malignant entities recognized by radiography should be referred for magnetic resonance imaging, which also serves as a preoperative local staging modality, with specific technical requirements. Indeterminate tumors, or tumors in which therapy depends on histology results, should be biopsied. For biopsy, we strongly recommend referral to a specialist regional sarcoma treatment center (RSTC), where a multidisciplinary tumor team, including a specialist pathologist, radiologist, and sarcoma surgeon, are involved. Additional staging modalities are entity specific and should be performed according to the recommendations of the RSTC.
Keywords: bone tumor; bone tumor mimickers; consensus statement; diagnostic algorithm; imaging methods; ESSR